STUDY OF VITAMIN D LEVELS IN EPILEPTIC CHILDREN IN AGE GROUP OF 2-16 YEARS - Patil, Nivedita; Rai, Shankar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: Epilepsy is a common neurological disorder in childhood. A number of medications are used in the treatment of epilepsy. Antiepileptic drugs (AEDs) are known to exert deleterious effects on vitamin D metabolism. Its deficiency state in epileptics can lead to difficult seizure control as vitamin D is said to have anti-epileptogenic activity in addition to its known role in calcium metabolism. Correction of vitamin D deficiency may help in decreasing the morbidity as well as seizure frequency. The purpose of this prospective observational study was to determine vitamin D status in these children. Methods: Seventy children aged 2-16 years with epilepsy on AEDs were assessed for vitamin D levels. Results: The results showed that the vitamin D levels in this study population were significantly low. Conclusion: Vitamin D levels were significantly low in children with epilepsy and hence, it is recommended that vitamin D supplementation in these children is necessary to reduce the seizure frequency and vitamin D deficiency related morbidity. Keywords: 25OH vitamin D, Epilepsy, Antiepileptic drugs Â 